Guidelines of the Polish Society of Pediatric Endocrinology and Diabetology and Pediatric Section of Diabetes Poland on insulin therapy using hybrid closed-loop systems in children and adolescents with diabetes in Poland - Agnieszka Szadkowska; Agata Chobot; Barbara Głowińska-Olszewska; Przemysława Jarosz-Chobot; Beata Mianowska; Małgorzata Myśliwiec; Agnieszka Szypowska; Agnieszka Zubkiewicz-Kucharska; Mieczysław Walczak (Pediatric Endocrinology, Diabetes and Metabolism)
Currently, hybrid closed loop (HCL) systems represent the most advantageous therapeutic option for people with diabetes requiring intensive insulin therapy. They make it possible to achieve optimal metabolic control of the disease in any age group while improving the quality of life of children and adolescents with diabetes and their families. Therefore, we present recommendations for the use of HCL systems in children and adolescents focusing on systems currently available in Poland. These systems should be the first choice in terms of method of insulin therapy in the paediatric population. They can be implemented at any stage of diabetes management. These recommendations are based on scientific evidence and experts' experience. They include principles for the initiation, optimisation, and ongoing management of HCL therapy, as well as the required HCL-related education.